Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams Social Services Developed Cash Benefit Paid in Great Britain [Picture] Each circle represents 10 million pounds Payments on this page are a measure of unemployment, as well as of the provision made for relieving it Payments on the opposite page are a measure of growing social care 32 33 15X/2/566/303